Self-efficacy differences in high school athletes and non-athletes by gender - Hoell, Michelle R. (My University, 2011)
Educational development is important for the success of society. Self-efficacy, or the belief that one can complete an activity successfully, has become an important attribute in the drive for successful students. This concept has broadened to look at the generalized effects of self-efficacy on the development of students. This study examined if generalized self-efficacy ratings differed between high school athletes and non-athletes and/or by gender. Previous research has indicated that participation in high school athletics has multiple benefits for students. In addition, the relationship between gender and self-efficacy has been the focus of many researchers and typically significant differences are found. This study was designed to expand the research base on generalized self-efficacy and how it varies depending on high school athletic status and gender. Data was collected from 516 students in the 11th and 12th grade utilizing self report measures. Results showed a significant effect of athletic status on generalized self-efficacy. High school athletes reported a significantly higher generalized self-efficacy rating than non-athletes. There was also a main effect of athletic status shown on subscale of talent on the MJSES of participation in athletics. Together with results of previous research, this study suggests school psychologists may play a crucial role evaluating general self-efficacy, and developing and monitoring interventions designed to increase self-efficacy.
Keywords: Prediction of scholastic success, Psychological aspects.; High school students, Psychology; Self-efficacy.